2008
DOI: 10.1007/s00244-007-9106-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Water Quality and Age on the Acute Toxicity of Copper to the Florida Apple Snail, Pomacea paludosa

Abstract: Copper (Cu)-containing compounds have been used in Florida as fungicides, herbicides, and soil amendments, resulting in elevated Cu in the aquatic ecosystem. The Florida apple snail (Pomacea paludosa), a key species in south Florida, may be adversely affected by Cu. Water-quality parameters, such as hardness, dissolved organic carbon (DOC), pH, and alkalinity, affect metal bioavailability and toxicity in aquatic organisms; however, it is uncertain to what extent these factors affect Cu toxicity in the Florida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…This indicates that DOC is an important factor that influences Cu uptake and Cu toxicity to the apple snail. A study conducted by Rogevich et al (2008) with apple snails found that the 96 h-LC50 for Cu increased with increasing DOC concentration. The influence of DOC on Cu toxicity was also found for other trace metals with other organisms (Hoang et al 2004;Sciera et al 2004;VanGenderen et al 2003;Ryan et al 2004;Schwartz et al 2004).…”
Section: Adult Uptake Studymentioning
confidence: 98%
See 1 more Smart Citation
“…This indicates that DOC is an important factor that influences Cu uptake and Cu toxicity to the apple snail. A study conducted by Rogevich et al (2008) with apple snails found that the 96 h-LC50 for Cu increased with increasing DOC concentration. The influence of DOC on Cu toxicity was also found for other trace metals with other organisms (Hoang et al 2004;Sciera et al 2004;VanGenderen et al 2003;Ryan et al 2004;Schwartz et al 2004).…”
Section: Adult Uptake Studymentioning
confidence: 98%
“…However, concentrations of dissolved organic carbon (DOC) were also high (up to 51 mg/l DOC) in overlying water. The presence of DOC will decrease Cu bioavailability (Ryan et al 2004;Sciera et al 2004;Rogevich et al 2008). Using the biotic ligand model (BLM) to estimate Cu bioavailability indicated that the bioavailable portion of Cu in the overlying water was low (DiToro et al 2000, Notten et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CuCO 3 was also suggested to be bioavailable to invertebrate species (De Schamphelaere and Janssen 2002). Rogevich et al (2008) indicate that CuCO 3 may be bioavailable to the Florida apple snail. Results of the present study indicated that the fraction of bioavailable Cu species in the overlying water of the first flooding were less than 1% of total Cu.…”
Section: Multiple Flooding Study: Copper Speciation and Bioavailabilitymentioning
confidence: 98%
“…Free cupric ion (Cu 2+ ) and Cu hydroxide (CuOH + ) are the two most bioavailable forms to aquatic organisms (Pagenkopf et al 1974, 1983, Santore et al 2001. Recent studies suggest that Cu carbonate (CuCO 3 ) is also bioavailable to invertebrate species (De Schamphelaere and Janssen 2002;Rogevich et al 2008). Agriculture soils usually contain DOC, carbonate salts, and other minerals which will also complex with Cu and influence Cu speciation and bioavailability (He et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory simulation and field monitoring studies had been conducted to examine the biogeochemical aspects of Cu in citrus groves soils and subsequent impacts on soil quality . Environmental concerns about the side effects of copper-ba.sed fungicides have addressed their potential for accumulation in soils and the effects on soil biota such as earthworms (Paoletti et al, 1994), nematodes (Jaworska and Gorczyca, 2002), and Florida apple snail (Rogevich et al, 2008). However, to date, minimal information is available regarding the changes in microbial properties in citrus grove soils due to the accumulation of excess Cu in soils from repeated use of Cucontaining fungicides.…”
mentioning
confidence: 99%